Renal Replacement Therapy for Acute Kidney Injury in COVID-19 Patients in Latin America - Claure Del Granado, Rolando; Casas Aparicio, Gustavo; Rosa Diez, Guillermo; Rizo Topete, Lilia María; Ponce, Daniela (Kidney Blood Press Res, 2020)
The incidence of acute kidney injury (AKI) in hospitalized patients with COVID-19 is broad and ranges from 0.5 to 29% according to early reports from China and Italy [1, 2]. A recent multicenter retrospective cohort in New York showed a higher incidence (37%) and mortality (35%). AKI was primarily seen in COVID-19 patients with respiratory failure; 89.7% of patients who were on mechanical ventilation developed AKI as compared to just 21.7% of non-ventilated patients. Furthermore, 96.8% of patients who required renal replacement therapy (RRT) were on ventilators [3]. From these first reports, AKI emerges at the same time as the acute respiratory distress syndrome, and the development of AKI is usually found in patients who progress to phase 3 of the extra-pulmonary systemic hyper-inflammation syndrome [4]. Hirsch et al. [3] reported that up to 37.3% of AKI cases occurred within the first 24 h of hospital admission, and AKI frequently coincides with the development of the hyperinflammation phase